Prospective European Survey on Atrial Fibrillation Ablation: Clinical Characteristics of Patients and Ablation Strategies Used in Different Countries. (8th July 2014) - THEMISTOCLAKIS, SAKIS; RAVIELE, ANTONIO; CHINA, PAOLO; PAPPONE, CARLO; PONTI, ROBERTO DE; REVISHVILI, AMIRAN; ALIOT, ETIENNE; KUCK, KARL‐HEINZ; HOFF, PER IVAR; SHAH, DIPEN; ALMENDRAL, JESÚS; MANOLIS, ANTONIS S.; et al.
Survey on Atrial Fibrillation Ablation Background Atrial fibrillation (AF) ablation is widely adopted. Our aim was to conduct a prospective multicenter survey to verify patients' characteristics, approaches, and technologies adopted across Europe. Methods and Results A total of 35 centers in 12 countries actively participated in the study and 940 patients (median age 60 years) were enrolled. AF was paroxysmal, persistent, and long‐lasting persistent in 52.4%, 36%, and 11.6% of patients, respectively; 95.5% of patients were symptomatic and 91.4% were refractory to antiarrhythmic therapy. Redo procedures were performed in 20.9%. Pulmonary vein isolation (PVI) emerged as the cornerstone of ablative therapy and has been performed in 98.7% of procedures, with confirmation of PVI in 92.9% of cases. The ablation of nonparoxysmal AF was not generally limited to isolating the PVs and several adjunctive approaches are adopted, particularly in the case of long‐lasting persistent AF. Linear lesions or elimination of complex fractionated atrial electrograms were more frequently added. Circular mapping catheters and imaging techniques were seen to be used in about two‐thirds of cases. Radiofrequency energy was delivered through open irrigated catheters in 68% of cases. Conclusions European centers are largely following the recommendations of the guidelines and the expert consensus documents for AF ablation. AF ablation is mainly performed in relatively young patients with symptomatic drug refractory AF and no or minimal heart disease. Patients with paroxysmal AF are the most frequently treated with a quite uniform ablative approach across Europe. A less standardized approach was observed in nonparoxysmal AF patients.